Research advances on reisistance to kiwifruit bacterial canker - ZHANG Min; SUN Leiming; FU Rong; LIN Miaomiao; WANG Ran; QI Xiujuan (Guoshu xuebao)
Kiwifruit (Actinidia spp.) is origin from China, comprising rich germplasm resources and wide geographical distribution. It is one of the most successful fruit crops domesticated in the 20th century and has taken an important place in the development of the fruit industry. China ranks first in the world in both planting area and yield and it becomes one of the advantageous characteristic industries in our country. Kiwifruit bacterial canker (KBC), which is caused by Pseudomonas syringae pv. actinidiae (Psa), is one of the most serious diseases that harm the kiwifruit industry. Since the first KBC was detected in Japan in 1984, it has been discovered in various countries around the world. It has become a major factor restricting the development of industries in the world. The typical symptoms of KBC include necrotic spots on leaves, wilting and ulceration on vines and twigs, withering of vine trunks, and with milky white or red mucus. It is highly virulent, explosive and infective, and once a vine has been systemically invaded, it may quickly lead to death. It has extremely strong infectivity and can spread in major production areas around the world in a short period of time. In spring or autumn, low temperatures can greatly favor the multiplication of the bacterium. Some plants, insect and pollen, agronomical techniques, as well as extreme weather phenomena, can contribute to further spreading. Psa manipulates plant hosts and promotes diseases by producing toxic effector factors (HopZ5 and AvrRpm1) through its TypeⅢsecretion system (T3SS). These toxic effectors can disrupt the immune defense response of plants, allowing patho-gens to quickly adapt to the host environment. The integrative and conjugative elements (ICEs) are large mobile elements, which can confer new phenotypes to Psa and are frequently implicated as the mechanism underlying antimicrobial resistance evolution in bacterial pathogens. According to genetic diversity and toxin production, Psa can be classified into six biovars (Psa1-Psa6). Psa4 is substantially different from other strains in that it has less aggressive ability and only cause leaf spots. Due to the difference in phenotypic, genetic and phylogenetic aspects, it was renamed P. syringae pv. actinidifoliorum (Pfm). In existing research, no effective cure for KBC has been found. The frequent application of streptomycin and copper agents for controlling Psa shows that multiple Psa lineages have acquired streptomycin or copper resistance genes. Therefore, breeding resistant varieties and enhancing the disease resistance of kiwifruit are effective measures to solve KBC. Through analysis of the morphological structure, physiological level and molecular level of kiwifruit, it is shown that different kiwifruits have different resistance to Psa. It was found that the overall resistance trend is that the resistance of A. arguta and A. eriantha is stronger than A. chinensis by different resistance identification. The use of hybrid breeding technology can achieve the combination of excellent traits and cultivate resistant varieties. However, the traditional hybrid breeding method is too time-consuming and complex, usually taking 10-15 years to develop a new variety. With the development of modern sequencing techniques, the emergence of molecular marker assisted breeding technology has greatly shortened the breeding period and improved breeding efficiency. The use of molecular marker technology to screen germplasm resources with excellent resistance has been widely applied in crop research, and there are also a few applications in kiwifruit. For example, using random amplified polymorphic DNA (RAPD) analysis found that the resistant strains all had a 1458 bp DNA fragment, while the susceptible strains did not have. Using SSR technology combined with BSA analysis method, the molecular marker screening of disease resistant genes (PR) was carried out, and SSR molecular marker UDK97-428116 linked to disease resistant genes was obtained. With advances in modern biotechnology, the use of high-density genetic maps for quantitative trait locus (QTL) mapping plays an important role in the research on agronomic traits. In recent years, the construction of genetic maps for fruit crops has developed rapidly and has been applied to many fruit crops, such as grapes, cherries and kiwifruit. The application of genetic mapping and QTL mapping technology plays an important role in the exploration of kiwifruit traits such as gender, fruit quality and disease resistance. Using high-density genetic and QTL mapping, a major single QTL for Psa resistance on linkage 27 was identified on Hort16A, and six minor QTLs were identified in P1. Moreover, it was discovered that the resistance in the F1 population was improved by additive effects from Hort16A and P1 QTLs, providing evidence for the resistance mechanism of kiwifruit. When Psa toxic effector factors are injected into the host plant, it triggers the immune defense response of plant, PTI (PAMP-triggered-immunity) and ETI (effector-triggered-immunity). Nucleotide binding and leucine rich repeat receptors (NLRs) are the largest family of immune receptors in plants. At present, multiple NLR proteins that recognize Psa effector factors have been identified, like RPA1 and NbPTR1. It has shown that many genes play important roles in the kiwifruit disease resistance response, such as PR1, NPR1, TGA, RIN4, FLS2 and WRKY22, providing new genetic resources for resistance breeding. It is critically important to understanding how pathogens emerge and what drives their adaptation to cause virulent disease. Exploring disease prevention and control technologies, and breeding new disease resistant varieties are of great significance for the development of this industry. The purpose is to review the latest progress in research on KBC and kiwifruit resistance, providing theoretical basis for kiwifruit resistance breeding.